Sobre a identidade do Centro de Educação Matemática (CEM): acidentes de uma leitura cartesiana - Silva, Heloísa da; Garnica, Antonio Vicente Marafioti [UNESP] (My University, 2011)
In this paper we present results of research conducted on the constitution of the identity of CEM (Centre for Mathematics Education), a group of mathematics teacher educators from the city of São Paulo, Brazil (1984-1997). We emphasize the processes of constitution of CEM’s identities, on the perspective of Oral History in Mathematics Education, of the Model of Semantic Fields and of theories of identities. As part of the broader endeavor of examining possibilities for constituting identities for the group, from several theoretical standpoints, here we report an exercise on constituting the identity of CEM from a Cartesian standpoint; the overall assumption is that we are not properly interested in what CEM is or was, but on the possibilities themselves. We argue that such analysis leads to an understanding of the group as being an accident involving the individual identities of its members but not to an understanding of CEM’s group identity as such.

O artigo apresenta alguns resultados da investigação realizada sobre a constituição da identidade do Centro de Educação Matemática (CEM), um grupo de educadores matemáticos da cidade de São Paulo atuante principalmente entre os anos de 1984 e 1997. Para configurar uma posição sobre a(s) identidade(s) do CEM são trazidos à cena o método da História Oral, o Modelo dos Campos Semânticos e teorias da identidade. Neste ensaio, ao assumir-se que o processo de constituição dessas identidades não se refere ao que o CEM é ou foi, mas a um conjunto de possibilidades de apreendê-lo a partir de estratégias e iniciativas desenvolvidas em determinadas condições e tempo, apresenta-se um exercício de constituir a identidade do CEM a partir de lentes cartesianas. Nesta experiência pondera-se que analisar, numa perspectiva cartesiana, a constituição da identidade desse grupo significa analisar o conjunto das identidades individuais que o formaram, revelando-o como um acidente atrelado a essas identidades.
Keywords: CEM; Mathematics Education; Identity; Oral History; Cartesian Standpoint; CEM; Educação Matemática; Identidade; História Oral; Leitura; Cartesiana